Chemical Components and Biological Effects of Genus Origanum - Li Zhou; Fatma Al-Zahra Kamal Kamel Attia; Lijun Meng; Sitan Chen; Zhenhua Liu; Changyang Ma; Lijun Liu; Wenyi Kang (Journal of Food Quality)
The plants from genus Origanum are common folk Chinese herbs used to treat a variety of diseases. They are also used as a spice, a seasoning, and an ornament. Origanum plants are rich in essential oils and also have other compounds including terpenoids, flavonoids, organic acids, and sterols. They have a variety of biological activities such as antispasmodic, anti-inflammatory, growth-promoting, antibacterial, antioxidant, and anticancer properties. The chemical components and biological effects of genus Origanum were summarized by different scientific databases such as Web of Science, SciFinder, Baidu Scholar, PubMed, ScienceDirect, and SpringerLink. In conclusion, recent studies were mainly focused on the activities of their essential oils. The research studies for nonvolatile constituents and their pharmacological activities are few. Therefore, research on compounds in genus Origanum plants can be strengthened and their application prospect can be explored so as to make better use of the resources of these plants.